Quantum dot-nano transparent ceramic fluorescent composite material and preparation method thereof
CsPbX3 quantum dots were embedded in γ-Al2O3 nano-transparent ceramics through high-pressure and low-temperature sintering, which solved the problem of poor stability of CsPbX3 quantum dots and achieved high stability and durability of CsPbX3@γ-Al2O3 quantum dot-nano-transparent ceramic composite materials, which are suitable for next-generation optoelectronic devices.
Patent Information
- Application Number
- CN202510916387.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-10-03
AI Technical Summary
CsPbX3 quantum dot materials have poor stability in environments such as light, heat and humidity, and are easily decomposed, affecting the luminous efficiency and color stability of LED devices. In addition, traditional packaging materials have problems such as unsatisfactory mechanical properties during application.
CsPbX3 quantum dots are embedded in γ-Al2O3 nano-transparent ceramics using high-pressure and low-temperature sintering to form CsPbX3@γ-Al2O3 quantum dot-nano-transparent ceramic fluorescent composite materials. The nanostructure of the ceramic matrix is used to limit the size of the quantum dots and provide mechanical strength, isolating them from external environmental erosion.
The stability and durability of the material are improved, the service life is extended, and it has good optical properties and environmental stability, making it suitable for the next generation of optoelectronic devices.
Smart Images

Figure CN120737844A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of quantum dot and transparent ceramic intersection materials, and specifically relates to a novel quantum dot-transparent ceramic composite material and a preparation method thereof, which has important application value in fluorescence-related fields such as lighting and display. Background Art
[0002] Inorganic perovskite (CsPbX3, X = Cl, Br, I) quantum dots (QDs) are a class of semiconductor materials with excellent optoelectronic properties. They typically exhibit exceptional properties, including high color purity, high fluorescence quantum efficiency, high carrier mobility, and continuously tunable emission position and color across the entire visible and near-infrared range. These properties have attracted significant attention both domestically and internationally due to their broad and potential applications in LEDs, solar cells, lasers, and photodetection. For example, CsPbX3 exhibits a luminescence quantum efficiency (PLQY) as high as 95%, a fluorescence lifetime as low as 1 ns, and a half-width (FWHM) less than 30 nm. Furthermore, the emission wavelength and color of CsPbX3 can be tuned by varying the ratio of different halogen anions. Despite these significant advantages, CsPbX3 QDs exhibit poor physical and chemical stability. Their luminescence properties are extremely sensitive to environmental factors such as temperature, humidity, and light irradiation. This can lead to gradual decomposition or phase transitions in LEDs over time, resulting in rapid decay of luminescence intensity and a shift in wavelength (color). Furthermore, when CsPbX3 containing different halogen components are mixed in the device, halogen ions migrate and exchange with each other, leading to broadening and shifting of certain emission peaks in white-light LEDs. This severely impacts the device's luminous efficiency, color stability, and other luminescent properties, significantly hindering its further development. Among these, iodine-containing red-emitting perovskite quantum dots have the worst luminescence stability, resulting in the most severe attenuation of red light in LED devices, thus affecting the color temperature and color rendering index of white-light LED devices. Therefore, effectively improving the stability of CsPbX3 quantum dot materials in environments such as light, heat, and humidity, and preventing anion exchange between different CsPbX3 quantum dots, are currently important issues that need to be addressed.
[0003] In order to improve the environmental stability of CsPbX3 quantum dots, domestic and foreign researchers have conducted detailed research on three aspects: ion doping, surface passivation, and coating composites. For example, Mn doping in CsPb(ClBr)3 quantum dots 2+ , not only produces red-orange light, but also has a PLQY of 65%, and its stability has been significantly improved. et al., Highly luminescent and stable perovskite nanocrystals with octylphosphonic acid as a ligand for efficient light-emitting diodes, ACS Applied Materials & Interfaces, 2018, 10 (4): 3784-3792] Octylphosphonic acid (OPA) was used to replace traditional oleic acid to prepare CsPbBr3 quantum dots. The prepared CsPbBr3-OPA quantum dots have high fluorescence efficiency. Moreover, after being placed at room temperature for 30 days, the luminescence intensity of the OPA-modified CsPbBr3 quantum dots still has 85% of the initial value, while the luminescence intensity of the traditional oleic acid-modified CsPbBr3 quantum dots shows a significant attenuation. Professor Zhang Qiao's team at Soochow University [Q. Zhong, M. Cao, H. Hu, D.Yang, M. Chen, et al. , One-pot synthesis of highly stable CsPbBr3@SiO2 core–shell nanoparticles, ACS Nano, 2018, 12 (8): 8579-8587] to prepare monodisperse CsPbX3 / SiO2 core–shell structured nanoparticles. The composite material showed strong stability in different environments, such as water, high humidity air (40°C, humidity 75%) and ultraviolet light. Some researchers also grew perovskite quantum dots in situ in glass, and the prepared CsPbX3@glass composite glass had good water resistance and heat stability. However, the inorganic porous / layered / network encapsulation materials currently used to encapsulate CsPbX3 quantum dots still have some problems in practical applications, such as low working life, poor tolerance, weak light efficiency, and unsatisfactory mechanical properties. These have, to a certain extent, constrained the development and application of CsPbX3 quantum dots and also posed more challenges to the comprehensive performance of CsPbX3 quantum dots. Compared to inorganic porous, layered, or network-like encapsulating matrix materials, in-situ encapsulation of CsPbX3 quantum dots into dense, isolated, inorganic nanocrystalline transparent ceramics (grain size <100nm) offers superior comprehensive stability against water, light, heat, oxygen, and other environmental factors. However, the stable and controllable production of CsPbX3 quantum dot-encapsulated nanocrystalline transparent ceramics with high physical and chemical stability, high strength, and high hardness remains a significant challenge. Summary of the Invention
[0004] The purpose of the present invention is to provide a novel CsPbX3@γ-Al2O3 quantum dot-nano transparent ceramic fluorescent composite material and a preparation method thereof. The quantum dot-nano transparent ceramic material prepared by this method is not only conducive to breaking through the limitations of the traditional solution method on the selection of the matrix, but also can break through the bottleneck of poor mechanical properties and low stability of traditional quantum dot materials. In addition, its preparation conditions are simple and easy to control, and it belongs to the field of high-tech quantum dot-transparent ceramic materials.
[0005] The present invention is achieved through the following technical solutions.
[0006] The quantum dot-nano transparent ceramic fluorescent composite material described in the present invention has a molecular formula of CsPbX3@γ-Al2O3, wherein X is Cl, Br or I.
[0007] The preparation method of the quantum dot-nano transparent ceramic fluorescent composite material of the present invention comprises the following steps.
[0008] S1. Prepare CsPbX3 / γ-Al2O3 composite powder.
[0009] 1) Add cesium salt to deionized water to prepare a raw material solution of Cs ions; add lead salt to deionized water to prepare a raw material solution of Pb ions.
[0010] 2) The two raw material solutions from step 1) above are stirred and heated on a magnetic stirrer at a molar ratio of 1:1 at a stirring speed of 400-700 rad / min and a heating temperature of 80-100°C until the raw materials are completely dissolved into a solution. Heating and stirring are then stopped to obtain a halide mixed solution.
[0011] 3) Add γ-Al2O3 powder to the halide mixed solution prepared in step 2) so that the halide mass percentage is 4 to 8 wt.% of γ-Al2O3. After thorough mixing and stirring, place the mixture in a constant temperature drying oven set at 80 to 120°C and dry it to obtain a mixed powder of CsPbX3 and γ-Al2O3.
[0012] S2, Preparation of CsPbX3 / γ-Al2O3 quantum dots-nano transparent ceramic fluorescent composite materials.
[0013] 1) Place the mixed powder of CsPbX3 and γ-Al2O3 prepared in S1 into a mortar and grind for 1 to 3 hours to ensure thorough mixing.
[0014] 2) After grinding, the mixed powder from step 1) is placed in a high-pressure cold sintering apparatus for low-temperature, high-pressure sintering. Initially, the mixed powder is sealed in a cold sintering mold. After encapsulation, the mold is heated to 100°C and held at a low temperature. Simultaneously, pressure is applied to the sample at a rate of 20-50 MPa / min. After the pressure reaches 0.8-1 GPa, the pressure is maintained for 10 minutes. After the pressure is maintained, the sample is heated to 350-450°C and held for 0.5-2 hours. After the pressure is maintained, the sample is gradually unloaded at a rate of 10-20 MPa / min. After the pressure is released to atmospheric pressure, the sample is slowly cooled to room temperature to obtain the CsPbX3 / γ-Al2O3 quantum dot-nano transparent ceramic composite.
[0015] Furthermore, the CsPbX3 / γ-Al2O3 composite powder in S1 is any one of CsPbCl3 / γ-Al2O3, CsPbBr3 / γ-Al2O3, and CsPbI3 / γ-Al2O3.
[0016] Furthermore, the cesium salt in S1 is any one of CsBr, CsCs, and CsI; and the lead salt is any one of PbBr2, PbCl2, and PbI2.
[0017] Furthermore, the average particle size of the γ-Al2O3 nanopowder described in S1 is 20-50 nm, and the specific surface area is 100-130 cm 2 / g.
[0018] Furthermore, the sintering conditions in S2 are high pressure of 0.8 to 1 GPa, temperature of 350 to 450° C., and calcination time of 0.5 to 2 h.
[0019] Furthermore, the pressurization rate in S2 is 20-50 MPa / min, and the pressure relief rate after the insulation is 10-20 MPa / min. The gradient unloading pressure flow first relieves the pressure to 0.6 GPa at a uniform pressure relief rate and then maintains the pressure for 10 minutes, then gradually relieves the pressure to 0.3 GPa and continues to maintain the pressure for 10 minutes, then quickly relieves the pressure to the pressure, and finally starts to cool down.
[0020] Compared with the prior art, the present invention has the following beneficial effects.
[0021] (1) The internal structure of nanocrystalline transparent ceramics is different from that of atoms and single crystals. There are small size effects, surface and interface effects, and quantum size effects inside. The present invention effectively utilizes the nanopores or grain boundaries of the nanocrystalline transparent ceramic matrix to promote the uniform nucleation and growth of perovskite quantum dots, and uses the nanostructure of the ceramic matrix to limit the size of quantum dots, prevent quantum dots from agglomerating, and avoid the uneven size distribution and agglomeration problems in conventional solution methods.
[0022] (2) This invention effectively addresses the poor stability and easy decomposition of CsPbX3 quantum dots by embedding cubic perovskite halide quantum dots into a spinel structure and further encapsulating the halide quantum dots in ceramic vacancies or grain boundaries using fluorescent nanocrystalline transparent ceramics. This also improves the overall stability and durability of the material. This new material not only exhibits excellent optical properties but also has good environmental stability and durability, and is expected to provide a solution that combines high optical performance with strong environmental tolerance for next-generation optoelectronic devices.
[0023] (3) This invention utilizes the excellent optoelectronic properties and tunable luminescence characteristics of CsPbX3, as well as the high transparency, good mechanical strength, and chemical stability of γ-Al2O3 nanocrystalline transparent ceramics, to form a new material system. This combination not only takes advantage of the optoelectronic advantages of CsPbX3 but also leverages the structural stability of γ-Al2O3, and is expected to develop a new quantum dot-transparent ceramic composite fluorescent material with high stability and wide color gamut for the next generation of high-performance display technology.
[0024] (4) The present invention uses high-pressure synthesis technology for the in-situ growth of perovskite quantum dots in a nano-transparent ceramic matrix. This not only breaks through the bottleneck of poor mechanical properties and low stability of traditional quantum dot materials, but also breaks through the limitations of traditional solution methods on matrix selection. It is an innovation in research methods.
[0025] (5) The present invention effectively compounds perovskite quantum dots with inorganic nano-transparent ceramics through the synergistic effect of high-pressure physical and chemical reactions, effectively isolating the CsPbX3 quantum dots from the external environment and extending the service life of the material. At the same time, the ceramic matrix also provides additional mechanical strength and thermal stability, making the material have potential in a wider range of application scenarios.
[0026] (5) The sintering preparation conditions of the CsPbX3 / γ-Al2O3 fluorescent transparent ceramics in the present invention are simple, which not only simplifies the process but also enables batch controllable preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1The XRD patterns of CsPbBr3 / γ-Al2O3 ceramics with different concentrations of CsPbBr3 halide (4%, 5%, 6%, 7%, 8%) in Example 1 are shown.
[0028] Figure 2 The XRD patterns of CsPbCl3 / γ-Al2O3 ceramics with different concentrations of CsPbCl3 halide (4%, 5%, 6%, 7%, 8%) in Example 1 are shown.
[0029] Figure 3 The XRD patterns of CsPbI3 / γ-Al2O3 ceramics with different concentrations of CsPbI3 halide (4%, 5%, 6%, 7%, 8%) in Example 1 are shown.
[0030] Figure 4 These are photos of CsPbBr3 / γ-Al2O3 ceramic samples with different CsPbBr3 halide concentrations (4%, 5%, 6%, 7%, 8%) in Example 1.
[0031] Figure 5 These are photos of CsPbCl3 / γ-Al2O3 ceramic samples with different CsPbCl3 concentrations (4%, 5%, 6%, 7%, 8%) in Example 2.
[0032] Figure 6 These are photos of CsPbI3 / γ-Al2O ceramic samples with different CsPbI3 concentrations (4%, 5%, 6%, 7%, 8%) in Example 3.
[0033] Figure 7 The transmission spectra of CsPbBr3 / γ-Al2O3 ceramic samples with different CsPbBr3 halide concentrations (4%, 5%, 6%, 7%, 8%) in Example 1 are shown.
[0034] Figure 8 The transmission spectra of CsPbClr3 / γ-Al2O3 ceramic samples with different CsPbCl3 halide concentrations (4%, 5%, 6%, 7%, 8%) in Example 2.
[0035] Figure 9 The transmission spectra of CsPbI3 / γ-Al2O3 ceramic samples with different CsPbI3 halide concentrations (4%, 5%, 6%, 7%, 8%) in Example 3.
[0036] Figure 10 PL emission spectra of CsPbBr3 / γ-Al2O3 ceramic samples with different CsPbBr3 halide concentrations (4%, 5%, 6%, 7%, 8%) in Example 1.
[0037] Figure 11PL emission spectra of CsPbCl3 / γ-Al2O3 ceramic samples with different CsPbCl3 halide concentrations (4%, 5%, 6%, 7%, 8%) in Example 2.
[0038] Figure 12 PL emission spectra of CsPbI3 / γ-Al2O3 ceramic samples with different CsPbI3 halide concentrations (4%, 5%, 6%, 7%, 8%) in Example 3. DETAILED DESCRIPTION
[0039] The present invention will be further described below by way of examples and accompanying drawings. In the following examples, the cesium salt and lead salt reagents are analytically pure reagents. Example 1
[0040] A preparation method of CsPbBr3@γ-Al2O3 fluorescent composite ceramics.
[0041] In this embodiment, γ-Al2O3 nanopowder is used as raw material, with an average particle size of 20 nm and a specific surface area of 100 cm 2 / g, and the method for preparing it for CsPbBr3@γ-Al2O3 fluorescent composite ceramics is as follows.
[0042] S1. Prepare CsPbBr3 / γ-Al2O3 composite powder.
[0043] 1) Weigh 0.0587 g of cesium bromide and 0.101 g of lead bromide in a molar ratio of 1:1 and add them to 50 mL of deionized water to prepare Cs ion and Pb ion raw material solutions, respectively.
[0044] 2) The two raw material solutions from step 1) above were mixed, placed on a magnetic stirrer, stirred and heated at a stirring speed of 400 rad / min and a heating temperature of 100°C until the raw materials were completely dissolved into a solution. The heating and stirring were then stopped to obtain a halide mixed solution.
[0045] 3) Add weighed γ-Al2O3 powder to the halide mixed solution prepared in step 2) above, at a halide mass percentage of 8 wt.%. After thorough mixing and stirring, place the mixture in a constant temperature drying oven set at 120°C and dry it to obtain a mixed powder containing CsPbBr3 and γ-Al2O3.
[0046] S2, Preparation of CsPbX3 / γ-Al2O3 quantum dots-nano transparent ceramic fluorescent composite materials.
[0047] 1) The mixed powder of CsPbBr3 and γ-Al2O3 prepared in S1 was placed in a mortar and ground for 1 h to ensure thorough mixing.
[0048] 2) After grinding, the mixed powder from step 1) is placed in a high-pressure cold sintering apparatus for low-temperature, high-pressure sintering. Initially, the mixed powder is sealed in a cold sintering mold. After encapsulation, the mold is heated to 100°C and held at a low temperature. Simultaneously, pressure is applied to the sample at a rate of 20 MPa / min. After reaching 0.8 GPa, the pressure is maintained for 10 minutes. After the pressure is maintained, the sample is heated to 350°C and held for 0.5 hours. After the pressure is maintained, the sample is gradually unloaded at a rate of 10 MPa / min. After the pressure is released to atmospheric pressure, the sample is slowly cooled to room temperature to obtain the CsPbBr3 / γ-Al2O3 quantum dot-nanotransparent ceramic composite.
[0049] The same steps were repeated above, but the halide mass percentage of γ-Al2O3 was set to 4 wt.%, 5 wt.%, 6 wt.%, and 7 wt.%, respectively, to obtain CsPbBr3 / γ-Al2O3 quantum dot-nano transparent ceramic composites with different halide mass percentages.
[0050] The CsPbBr3 / γ-Al2O3 quantum dots-nano transparent ceramic composite materials obtained above under different halide mass percentage conditions were detected by X-ray diffractometer (D / max-rA type rotating target, Cu-Kα radiation, 40kv×1100mA), and the XRD curves are shown in Figure 1 It can be seen that the sintered products prepared in this example are all CsPbBr3 / γ-Al2O3 phase. The actual photo of CsPbBr3 / γ-Al2O3 quantum dots-nano transparent ceramic after high pressure and low temperature sintering is shown in the figure. Figure 2 As shown, the transmission spectrum is Figure 3 As shown by Figure 2 and Figure 3 It can be seen that the transmittance of the sintered composite ceramic product prepared in this embodiment is about 50% in the 500-2500 nm wavelength range. Figure 4 is the emission spectrum of the sintered composite ceramic product prepared in this embodiment, Figure 4 It can be seen that the emission band of the CsPbBr3 / γ-Al2O3 quantum dot-nano transparent ceramic sample with a doping mass fraction ratio of 8 wt.% prepared in this example is similar to the emission spectrum of a single CsPbBr3 quantum dot, indicating that the CsPbBr3 / γ-Al2O3 quantum dot-nano transparent ceramic composite fluorescent material can be successfully prepared through this example. Example 2
[0051] A preparation method of CsPbCl3@γ-Al2O3 fluorescent composite ceramics.
[0052] In this embodiment, γ-Al2O3 nanopowder is used as raw material, with an average particle size of 30 nm and a specific surface area of 110 cm 2 / g, and the method for preparing it for CsPbCl3@γ-Al2O3 fluorescent composite ceramics is as follows.
[0053] S1. Prepare CsPbCl3 / γ-Al2O3 composite powder.
[0054] 1) Weigh 0.0603 g of cesium chloride and 0.0996 g of lead chloride in a molar ratio of 1:1 and add them to 50 mL of deionized water to prepare Cs ion and Pb ion raw material solutions, respectively.
[0055] 2) The two raw material solutions from step 1) above were mixed, placed on a magnetic stirrer, stirred and heated at a stirring speed of 500 rad / min and a heating temperature of 90°C until the raw materials were completely dissolved into a solution. The heating and stirring were stopped to obtain a halide mixed solution.
[0056] 3) Add weighed γ-Al2O3 powder to the halide mixed solution prepared in step 2) so that the halide content is 8 wt.% of γ-Al2O3. After thorough mixing and stirring, place the mixture in a constant temperature drying oven at 100°C and dry it to obtain a mixed powder containing CsPbCl3 and γ-Al2O3.
[0057] Preparation of S2, CsPbCl3 / γ-Al2O3 quantum dots-nano transparent ceramic fluorescent composite materials.
[0058] 1) The mixed powder of CsPbCl3 and γ-Al2O3 prepared in S1 was placed in a mortar and ground for 2 h to ensure thorough mixing.
[0059] 2) After grinding, the mixed powder from step 1) is placed in a high-pressure cold sintering apparatus for low-temperature, high-pressure sintering. Initially, the mixed powder is sealed in a cold sintering mold. After encapsulation, the mold is heated to 100°C and held at a low temperature. Simultaneously, pressure is applied to the sample at a rate of 30 MPa / min. After reaching 1 GPa, the pressure is maintained for 10 minutes. After the pressure is maintained, the sample is heated to 400°C and held for 1 hour. After the pressure is maintained, the sample is gradually unloaded at a rate of 15 MPa / min. After the pressure is unloaded to atmospheric pressure, the sample is slowly cooled to room temperature to obtain the CsPbCl₃ / γ-Al₂O₃ quantum dot-nano transparent ceramic composite.
[0060] The same steps were repeated above, but the halide mass percentage of γ-Al2O3 was set to 4 wt.%, 5 wt.%, 6 wt.%, and 7 wt.%, respectively, to obtain CsPbCl3 / γ-Al2O3 quantum dot-nano transparent ceramic composite materials with different halide mass percentages.
[0061] The CsPbCl3 / γ-Al2O3 quantum dots-nano transparent ceramic composites obtained above under different halide mass percentage conditions were detected by X-ray diffractometer (D / max-rA type rotating target, Cu-Kα radiation, 40kv×1100mA), and the XRD curves are shown in Figure 1 It can be seen that the sintered products prepared in this example are all CsPbCl3 / γ-Al2O3 phase. The actual photo of CsPbCl3 / γ-Al2O3 quantum dots-nano transparent ceramic after high pressure and low temperature sintering is shown in the figure. Figure 2 As shown, the transmission spectrum is Figure 3 As shown by Figure 2 and Figure 3 It can be seen that the transmittance of the sintered composite ceramic product prepared in this embodiment is 10% to 40% in the 500 to 2500 nm wavelength range. Figure 4 is the emission spectrum of the sintered composite ceramic product prepared in this embodiment, Figure 4 It can be seen that the emission band of the CsPbCl3 / γ-Al2O3 quantum dot-nano transparent ceramic sample with a doping mass fraction ratio of 4 wt.% prepared in this example is similar to the emission spectrum of a single CsPbCl3 quantum dot, indicating that the CsPbCl3 / γ-Al2O3 quantum dot-nano transparent ceramic composite fluorescent material can be successfully prepared through this example. Example 3
[0062] A preparation method of CsPbI3@γ-Al2O3 fluorescent composite ceramics.
[0063] In this embodiment, γ-Al2O3 nanopowder is used as raw material, with an average particle size of 50 nm and a specific surface area of 120 cm 2 / g, and the method for preparing it for CsPbI3@γ-Al2O3 fluorescent composite ceramics is as follows.
[0064] S1. Prepare CsPbI3 / γ-Al2O3 composite powder.
[0065] According to the molar ratio of cesium iodide to lead iodide being 1:1, 0.0577 g of cesium iodide and 0.102 g of lead iodide were weighed and added into 50 mL of deionized water respectively to prepare a raw material solution of Cs ions and a raw material solution of Pb ions.
[0066] 2) The two raw material solutions from step 1) above were mixed, placed on a magnetic stirrer, stirred and heated at a stirring speed of 600 rad / min and a heating temperature of 100°C until the raw materials were completely dissolved into a solution. The heating and stirring were then stopped to obtain a halide mixed solution.
[0067] 3) Add γ-Al2O3 powder to the halide mixed solution prepared in step 2) above so that the halide content is 8 wt.% of γ-Al2O3. After thorough mixing and stirring, place the mixture in a constant temperature drying oven set at 100°C and dry it to obtain a mixed powder containing CsPbI3 and γ-Al2O3.
[0068] S2, Preparation of CsPbI3 / γ-Al2O3 quantum dots-nano transparent ceramic fluorescent composite materials.
[0069] 1) The mixed powder of CsPbI3 and γ-Al2O3 prepared in S1 was placed in a mortar and ground for 3 h to ensure thorough mixing.
[0070] 2) After grinding, the mixed powder from step 1) is placed in a high-pressure cold sintering apparatus for low-temperature, high-pressure sintering. Initially, the mixed powder is sealed in a cold sintering mold. After encapsulation, the mold is heated to 100°C and held at a low temperature. Simultaneously, pressure is applied to the sample at a rate of 50 MPa / min. After reaching 0.9 GPa, the pressure is maintained for 10 minutes. After the pressure is maintained, the sample is heated to 450°C and held for 2 hours. After the pressure is maintained, the sample is gradually unloaded at a rate of 20 MPa / min. After the pressure is unloaded to atmospheric pressure, the sample is slowly cooled to room temperature to obtain the CsPbI3 / γ-Al2O3 quantum dot-nanotransparent ceramic composite.
[0071] The same steps were repeated above, but the halide mass percentage of γ-Al2O3 was set to 4 wt.%, 5 wt.%, 6 wt.%, and 7 wt.%, respectively, to obtain CsPbI3 / γ-Al2O3 quantum dot-nano transparent ceramic composites with different halide mass percentages.
[0072] The CsPbI3 / γ-Al2O3 quantum dots-nano transparent ceramic composites obtained above under different halide mass percentage conditions were detected by X-ray diffractometer (D / max-rA type rotating target, Cu-Kα radiation, 40kv×1100mA), and the XRD curves are shown in Figure 1 It can be seen that the sintered products prepared in this example are all CsPbI3 / γ-Al2O3 phase. The actual photo of CsPbI3 / γ-Al2O3 quantum dots-nano transparent ceramic after high pressure and low temperature sintering is shown in the figure. Figure 2 As shown, the transmission spectrum is Figure 3 As shown by Figure 2 and Figure 3 It can be seen that the transmittance of the sintered composite ceramic product prepared in this embodiment is 40% to 60% in the 500 to 2500 nm wavelength range. Figure 4 is the emission spectrum of the composite ceramic product prepared in this embodiment, Figure 4 It can be seen that the emission band of the CsPbI3 / γ-Al2O3 quantum dot-nano transparent ceramic sample with a doping mass fraction ratio of 6 wt.% prepared in this embodiment is similar to the emission spectrum of a single CsPbI3 quantum dot, indicating that the CsPbI3 / γ-Al2O3 quantum dot-nano transparent ceramic composite fluorescent material can be successfully prepared through this embodiment.
[0073] Through the above examples 1, 2 and 3, the results show that the quantum dot-like emission CsPbX3 / γ-Al2O3 quantum dot-nano transparent ceramic composite fluorescent material can be successfully prepared by high pressure and low temperature sintering.
Claims
1. A quantum dot-nano transparent ceramic fluorescent composite material, characterized by The molecular formula is CsPbX3@γ-Al2O3, where X is Cl, Br or I.
2. The method for preparing a quantum dot-nano transparent ceramic fluorescent composite material according to claim 1, characterized in that The steps include: S1. Preparation of CsPbX3 / γ-Al2O3 composite powder: 1) Add cesium salt to deionized water to prepare a raw material solution of Cs ions; add lead salt to deionized water to prepare a raw material solution of Pb ions; 2) The two raw material solutions from step 1) above are stirred and heated on a magnetic stirrer at a molar ratio of 1:1 at a stirring speed of 400-700 rad / min and a heating temperature of 80-100°C until the raw materials are completely dissolved into a solution. Heating and stirring are then stopped to obtain a halide mixed solution. 3) Adding γ-Al2O3 powder to the halide mixed solution prepared in step 2) in an amount such that the halide is 4 to 8 wt.% of γ-Al2O3 by mass, thoroughly mixing and stirring, placing the mixture in a constant temperature drying oven set at 80 to 120°C, and drying to obtain a mixed powder of CsPbX3 and γ-Al2O3; Preparation of S2, CsPbX3 / γ-Al2O3 quantum dots-nano transparent ceramic fluorescent composite materials: 1) Grind the mixed powder of CsPbX3 and γ-Al2O3 prepared in S1 in a mortar for 1-3 h to fully mix. 2) After grinding, the mixed powder of step 1) is placed in a high-pressure cold sintering device for low-temperature and high-pressure sintering. At the initial stage of sintering, the mixed powder is first placed in a cold sintering mold for sealing and packaging. After packaging, the mold is first heated to 100°C and kept in a low-temperature insulation stage; at the same time, pressure is applied to the sample at a rate of 20 to 50 MPa / min. After the pressure is increased to 0.8 to 1 GPa, pressure is maintained for 10 minutes. After the pressure is maintained, the sample is heated to 350 to 450°C and maintained for 0.5 to 2 h. After the insulation is completed, the pressure is gradually unloaded at a rate of 10 to 20 MPa / min. After the pressure is unloaded to atmospheric pressure, the sample is slowly cooled to room temperature to obtain a CsPbX3 / γ-Al2O3 quantum dot-nano transparent ceramic composite material.
3. The method for preparing a quantum dot-nano transparent ceramic fluorescent composite material according to claim 1, characterized in that: The cesium salt in S1 is any one of CsBr, CsCs, and CsI; and the lead salt is any one of PbBr2, PbCl2, and PbI2.
4. The method for preparing a quantum dot-nano transparent ceramic fluorescent composite material according to claim 1, characterized in that: The average particle size of the γ-Al2O3 nanopowder described in S1 is 20-50 nm, and the specific surface area is 100-130 cm 2 / g.
5. The method for preparing a quantum dot-nano transparent ceramic fluorescent composite material according to claim 1, wherein the sintering conditions in S2 are a high pressure of 0.8 to 1 GPa, a temperature of 350 to 450°C, and a calcination time of 0.5 to 2 h.
6. The method for preparing a quantum dot-nano transparent ceramic fluorescent composite material according to claim 1, wherein S2 The medium pressurization rate is 20-50 MPa / min, and the pressure relief rate after the insulation is 10-20 MPa / min. The gradient unloading pressure flow first relieves the pressure to 0.6 GPa at a uniform pressure relief rate and then maintains the pressure for 10 minutes, then gradually relieves the pressure to 0.3 GPa and continues to maintain the pressure for 10 minutes, then quickly relieves the pressure to the pressure, and finally starts to cool down.